1960
DOI: 10.1063/1.1735380
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of Efficiency of Thermoelectric Devices

Abstract: A procedure has been developed for the exact calculation of the efficiency of thermoelectric generators and cooling devices in which the parameters of the materials have arbitrary temperature dependence. High speed computer techniques are found necessary. Approximate methods are reviewed and their discussion extended. A number of examples are worked out by both the exact and approximate methods. Comparison of these results show that the approximate methods agree with the exact method to about 5% in the case of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(66 citation statements)
references
References 3 publications
3
63
0
Order By: Relevance
“…Minor improvements in thermoelectric cooling beyond increasing average zT by increasing the Thomson effect in a functionally graded material were predicted as early as 1960 7 . Similarly Müller et al describe modest gains in cooling from functionally grading [8][9][10] where material properties are allowed to vary in a constrained way such that the average zT remains constant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Minor improvements in thermoelectric cooling beyond increasing average zT by increasing the Thomson effect in a functionally graded material were predicted as early as 1960 7 . Similarly Müller et al describe modest gains in cooling from functionally grading [8][9][10] where material properties are allowed to vary in a constrained way such that the average zT remains constant.…”
Section: Discussionmentioning
confidence: 99%
“…Early theoretical work by Sherman et al for TEC found that different ∆T max could be predicted from materials have the same or similar average zT but different temperature dependence of the individual properties α, ρ, κ 7 . This demonstrated that optimizing cooler performance is significantly more complex than simply maximizing zT .…”
Section: Introductionmentioning
confidence: 99%
“…For a small selection we draw the reader's attention to [24,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]. Another work should be particularly emphasized: Sherman, Heikes and Ure stated in [47] that the conditions which maximize the TEG's efficiency are precisely the conditions which minimize the irreversibility process, allowing a closer approach to the Carnot cycle where entropy production is zero. This concept had been deepened by Clingman [49,50] for TEG and TEC.…”
Section: Historical Notesmentioning
confidence: 99%
“…Recent work [1][2][3][4][5] has yielded powerful numerical algorithms and one dimensional (1D) models, which identify TEG configurations with maximized power output and efficiency for homogeneous, functionally graded and segmented thermoelectric materials. Those studies complemented the continua-theoretical description of thermoelectric pellets by an analytical approach, which is related to the relative current density.…”
Section: Introductionmentioning
confidence: 99%